Efektivitas Penggunaan Media Finger Painting Terhadap Kemampuan Menulis Permulaan Anak Usia Dini 5-6 Tahun di Tkq An-Namlu Karawang - Vicky Widyananda; Astuti Darmiyanti; Feronica Eka Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of finger painting media on children's writing skills. This study used an experimental methodology with a sample of 10 children aged 5-6 years from group B, using a one-group pre-test-post-test design. The survey was conducted 10 times in class B TKQ An-Namlu Karawang. According to survey findings and data analysis, early childhood writing skills improved by 34 and 57 points on pretest and posttest, respectively. The findings of the Paired Sample T-Test table show the t-count value of 36,037 and sig (0.000). Therefore, it can be said that finger painting media has a significant influence on children aged 5-6 years.